High Permeability Zone On Geothermal Manifestations Using Fault Fracture Density In Sembalun Area, Lombok - Agung, Yusuf Zaki; Haryanto, Agus Didit; Hardiyono, Adi; Setiawan, Dede Iim; Suleman, Widya Asoka (Journal of Geological Sciences and Applied Geology, 2021)
Geothermal manifestations can occur in zones of high permeability. Permeability zones can be analyzed through lineament density, assumed to be associated with faults and fractures which are considered as weak areas that can allow geothermal fluid to pass from reservoir to the surface. This study intends to determine the zone with high permeability in geothermal manifestations. Modeling of surface data in the form of lineament pattern can be analyzed with Fault Fracture Density (FFD) analysis. The lineaments pattern is obtained based on the appearance through DEMNAS satellite imagery. The lineaments pattern deliniated by providing lighting from several angles, from lighting azimuths of 0°, 60°, 120°, 180°, 240° and 300° at a constant altitude of 45°. FFD analysis shows geothermal manifestations appear in the high permeability zone in the Sembalun area, Lombok.